Mediação & arbitragem - um (des)equilibrio no acesso à actividade? - Rebelo, Mafalda Alexandra Alcaide (2021)
Alternative dispute resolution is increasingly gaining relevance in today's world, in particular arbitration and mediation. This is due to the judicial system’s slowness, not in line with the parties' demands for prompt resolution of their conflicts. This is especially true in a globalized world where legal and economic traffic is quite intense. Hence, a new professional market has emerged, in which mediators and arbitrators are the main actors. This thesis analyses the legal requirements to access the professional activity of mediator and arbitrator, in particular the following question: What legally justifies the requirement of a training certification for a mediator, who only assists the parties to reach an agreement, while there is an absence of a similar requirement to arbitrators, who are responsible to judge and decide a conflict? The answer to this question involved an approach: (i) to the functions and powers of the mediator and the arbitrator; (ii) to the legal regime of access to their respective activities and (iii) a critical analysis of the arguments of this Portuguese legislative option. Additionally, it issupported by the current and past legislation, by the pertinent bibliography, by interviews with academics and by inquiries prepared for arbitrators and mediators. In this investigation it was concluded that there is a clear imbalance and disproportion in the Portuguese legislative option, regarding the private system of mediation and arbitration. Also, it is concluded that the existence of these requirements in the public system of mediation is justified by the legal areas in which they act and the intervention of the State in entities if by managed. However, the extrapolation of the certified training requirement to the private system gives rise to an incoherence of values, since none of the arguments mentioned is able to justify the manifest imbalance of the requirements of access to the activity of private mediator in comparison to the requirements of access to taxes for the arbitrators. Therefore, an alternative legislation is suggested in this thesis, in order to ensure an equilibrium between these alternative dispute resolution, extending the requirement of specific training to arbitration, remedying the contradiction that is observed at the moment.